Nano precipitated phase reinforced binder gradient hard composite material and preparation method thereof
By using nano-precipitation phase-reinforced adhesive gradient hard composite materials in cemented carbide, the problems of insufficient performance of cemented carbide and difficult to coordinate hardness and toughness under harsh working conditions are solved, and the comprehensive performance of the material is improved.
Patent Information
- Application Number
- CN202411761018.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
Cemented carbides are difficult to meet the performance requirements of harsh working conditions, and hardness and toughness are difficult to coordinate.
The nano-precipitation phase-strengthening adhesive gradient hard composite material is used. By mixing AlN powder, WC powder, metal binder and carbide in a specific proportion, and processing it through ball milling, drying, drying and sintering, a material with surface hard phase enrichment, high core binder content and gradient distribution is formed.
It achieves a good combination of hardness and toughness of hard composite materials, improves the comprehensive performance of the material, and can more effectively meet the performance requirements under harsh working conditions.
Smart Images

Figure CN119571167A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material science and engineering technology, and in particular relates to a nano-precipitated phase reinforced binder gradient hard composite material and a preparation method thereof. Background Art
[0002] Cemented carbide is known as the "teeth of industry" due to its excellent properties such as high hardness, high strength, high wear resistance, high corrosion resistance, low thermal expansion coefficient and high chemical stability. It is widely used in cutting, geological exploration, mining, oil drilling, mold manufacturing and other fields. Cemented carbide materials are mainly composed of WC as a hard phase and Co as a binder. Among them, WC gives the alloy excellent wear resistance and load-bearing capacity, and Co enhances the impact resistance of the alloy.
[0003] The traditional Co-based binder itself has insufficient performance and is difficult to meet the stringent performance requirements of harsh working conditions such as oxidation, corrosion and high temperature, which limits the industrial application scope of cemented carbide. In addition, due to the large differences in thermal expansion coefficient, elastic modulus, Poisson's ratio and other properties between the WC-based hard phase and the Co-based binder, the overall hardness and toughness of cemented carbide are still difficult to coordinate during service.
[0004] Therefore, a nano-precipitation phase reinforced binder gradient hard composite material and a preparation method thereof are developed to solve the technical defects in the prior art that cemented carbide has difficulty meeting the performance requirements of harsh working conditions and difficulty in coordinating hardness and toughness, which has become an urgent problem to be solved by technical personnel in this field. Summary of the invention
[0005] Based on this, it is necessary to provide a nano-precipitation phase reinforced binder gradient hard composite material and a preparation method thereof, in view of the technical defects in existing technologies, such as the difficulty in meeting the performance requirements of harsh working conditions and the difficulty in coordinating hardness and toughness.
[0006] The present application provides a nano-precipitated phase-reinforced binder gradient hard composite material, the raw materials of the composite material include: AlN powder, WC powder and a metal binder, the metal binder includes: Co and / or Ni;
[0007] In terms of mass percentage, in the metal binder, the amount of Co element is 15-30wt% of the composite material, and the amount of Ni element is 15-30wt% of the composite material.
[0008] In one of the embodiments, in the metal binder, the amount of Co element is 20-25wt% of the composite material, and the amount of Ni element is 20-25wt% of the composite material, in terms of mass percentage.
[0009] In one of the embodiments, the method further includes: carbide, wherein the carbide includes TaC and / or NbC.
[0010] In one of the embodiments, the amount of transition metal elements in the carbide is 2-8 wt% of the composite material.
[0011] In one of the embodiments, the amount of transition metal elements in the carbide is 4-6wt% of the composite material.
[0012] In one of the embodiments, the amount of aluminum element in the AlN powder is 2-6 wt % of the composite material, in terms of mass percentage.
[0013] In one of the embodiments, the amount of aluminum element in the AlN powder is 3-5 wt% of the composite material in terms of mass percentage.
[0014] The present application also provides a method for preparing the composite material comprising any one of the above, the method comprising:
[0015] Step 1, raw material mixing: the raw materials are mixed to obtain the first product;
[0016] Step 2, ball milling and drying: the first product is ball milled and then dried to obtain the second product;
[0017] Step 3, dry pressing: the second product is pressed into a green compact to obtain the third product:
[0018] Step 4: Sintering: The third product is sintered under vacuum conditions to obtain a product.
[0019] In one embodiment, in step 4, the sintering needs to undergo denitrification pretreatment.
[0020] In one of the embodiments, the denitrification pretreatment method is: the third product is heated to 1200-1250°C at a heating rate of 5-10°C / min, and the temperature is maintained for 60-120 minutes.
[0021] In one of the embodiments, the sintering method is: heating the temperature to 1300-1400° C. at a heating rate of 2-5° C. / min, and maintaining the temperature for 30-120 min.
[0022] In summary, the nano-precipitated phase reinforced binder gradient hard composite material provided by the present application, the raw materials of the composite material include: AlN powder, WC powder, metal binder and carbide, and the feeding amount of aluminum element in AlN powder is 2-6wt% composite material by mass percentage. The present application also provides a preparation method of the above composite material, including: raw material mixing, ball milling drying, dry pressing and sintering. In the technical scheme provided by the present application, a gradient hard composite material with surface hard phase enrichment, high core binder content and gradient distribution at micrometer scale is prepared through the innovative design of raw materials and preparation methods; a nano-scale precipitated phase gradient distribution can also be formed in the binder through different sintering temperatures; the gradient distribution of hard phase-binder at micrometer scale and the gradient distribution of ordered γ' precipitated phase in the binder at nanometer scale are coupled and synergistically strengthened to achieve the improvement of comprehensive performance of the product; thereby effectively solving the technical defects in the prior art that cemented carbide is difficult to meet the performance requirements of harsh working conditions and hardness and toughness are difficult to coordinate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0024] Figure 1 In the technical solution provided in the embodiment of the present application, the element contents of Al and W on the surface and in the core of the WC-25Co-25Ni-3Al sample;
[0025] Figure 2 In the technical solution provided for the embodiments of the present application, the BSE images of (a) WC-25Co-25Ni-3Al, (b) WC-25Co-25Ni-3Al-8Ta and (c) WC-25Co-25Ni-3Al-8Nb samples show the gradient zone from the surface to the core of the sample;
[0026] Figure 3 In the technical solution provided in the embodiment of the present application, SEM images of the binder of the WC-25Co-25Ni-3Al sample, wherein (a) and (b) are binders close to the surface, and (c) and (d) are binders in the core;
[0027] Figure 4In the technical solution provided for the embodiments of the present application, the macroscopic Vickers hardness HV0.2 distribution diagram from the surface to the core of (a) WC-25Co-25Ni-3Al, (b) WC-25Co-25Ni-3Al-8Ta and (c) WC-25Co-25Ni-3Al-8Nb samples;
[0028] Figure 5 In the technical solution provided for the embodiment of the present application, the micro-Vickers hardness HV0.01 distribution diagram of the samples sintered at 1350°C from the surface to the core binder of (a) WC-25Co-25Ni-3Al, (b) WC-25Co-25Ni-3Al-8Ta, (c) WC-25Co-25Ni-3Al-8Nb, and WC-25Co-25Ni;
[0029] Figure 6 In the technical solution provided for the embodiment of the present application, the micro Vickers hardness HV0.01 distribution diagram of the binder from the surface to the core of (a) WC-25Co-25Ni-3Al, (b) WC-25Co-25Ni-3Al-8Ta and (c) WC-25Co-25Ni-3Al-8Nb samples sintered at 1320°C;
[0030] Figure 7 In the technical solution provided in the embodiment of the present application, a schematic flow chart of a method for preparing a nano-precipitated phase reinforced binder gradient hard composite material. DETAILED DESCRIPTION
[0031] The embodiments of the present application provide a nano-precipitation phase reinforced binder gradient hard composite material and a preparation method thereof, which are used to solve the technical defects in the prior art that cemented carbide has difficulty in meeting the performance requirements of harsh working conditions and has difficulty in coordinating hardness and toughness.
[0032] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0033] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0034] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0035] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0036] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0037] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0038] The following will be combined Figure 7 According to the nano-precipitated phase reinforced binder gradient hard composite material and the preparation method thereof provided in the present application, the gradient hard composite material is produced and prepared.
[0039] Example 1
[0040] This embodiment is a specific embodiment of preparing a gradient hard composite material product 1.
[0041] Step 1: Mix the raw materials
[0042] WC, Co, Ni and AlN are mixed in the following mass percentages to obtain a first product 1;
[0043] WC: 45.44%; Co: 25%; Ni: 25%; AlN: 4.56%;
[0044] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, and AlN powders is ≥99.9%, and the particle size is 1-3μm.
[0045] Step 2: Ball mill drying
[0046] The first product 1 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 1.
[0047] Step 3: Dry pressing
[0048] The second product 1 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 1.
[0049] Step 4: Sintering
[0050] The third product 1 is placed in a graphite crucible and sintered in a vacuum to obtain product 1.
[0051] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0052] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0053] The vacuum sintering method is: heating from 1230°C to 1350°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0054] In this embodiment, a gradient hard composite material product 1 having a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 1 reaches 4.61 GPa, and the core binder hardness HV0.01 reaches 5.99 GPa.
[0055] The microhardness HV0.01 distribution of the binder from the surface to the core of product 1 is as follows Figure 5 As shown in (a), Figure 5 It can be concluded that the hardness of the adhesive near the surface of product 1 is relatively low, and the hardness of the adhesive gradually increases with the increase in depth from the surface.
[0056] In addition, compared with pure WC-Co-Ni cemented carbide without γ' precipitation phase strengthened binder, the binder hardness of Product 1 is significantly improved.
[0057] Example 2
[0058] This embodiment is a specific embodiment of preparing a gradient hard composite material product 2.
[0059] Step 1: Mix the raw materials
[0060] WC, Co, Ni, AlN and TaC are mixed in the following mass percentages to obtain a first product 2;
[0061] WC: 36.91%; Co: 25%; Ni: 25%; AlN: 4.56%; TaC: 8.53%;
[0062] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, AlN, and TaC powders is ≥99.9%, and the particle size is 1-3μm.
[0063] Step 2: Ball mill drying
[0064] The first product 2 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80°C for 8 hours to obtain the second product 2.
[0065] Step 3: Dry pressing
[0066] The second product 2 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 2.
[0067] Step 4: Sintering
[0068] The third product 2 is placed in a graphite crucible and sintered in a vacuum to obtain product 2.
[0069] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0070] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0071] The vacuum sintering method is: heating from 1230°C to 1350°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0072] In this embodiment, a gradient hard composite material product 2 having a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 2 reaches 5.08 GPa, and the core binder hardness HV0.01 reaches 6.06 GPa.
[0073] The microhardness HV0.01 distribution of the binder from the surface to the core of product 2 is as follows Figure 5 As shown in (b), Figure 5 It can be concluded that although the binder hardness near the surface and core of product 2 does not show an obvious hardness gradient distribution like product 1, the binder hardness near the surface of product 1 has been improved to a certain extent. In addition, compared with pure WC-Co-Ni cemented carbide without γ' precipitation phase strengthened binder, the binder hardness of product 2 has been significantly improved.
[0074] Example 3
[0075] This embodiment is a specific embodiment of preparing a gradient hard composite material product 3.
[0076] Step 1: Mix the raw materials
[0077] WC, Co, Ni, AlN and NbC are mixed in the following mass percentages to obtain a first product 3;
[0078] WC: 36.41%; Co: 25%; Ni: 25%; AlN: 4.56%; NbC: 9.03%;
[0079] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, AlN, and NbC powders is ≥99.9%, and the particle size is 1-3μm.
[0080] Step 2: Ball mill drying
[0081] The first product 3 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 3.
[0082] Step 3: Dry pressing
[0083] The second product 3 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 3.
[0084] Step 4: Sintering
[0085] The third product 3 is placed in a graphite crucible and sintered in a vacuum to obtain product 3.
[0086] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0087] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0088] The vacuum sintering method is: heating from 1230°C to 1350°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0089] In this embodiment, a gradient hard composite material product 3 having a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of the sample of product 3 reaches 5.72GPa, and the core binder hardness HV0.01 reaches 6.02GPa.
[0090] The microhardness HV0.01 distribution of the binder from the surface to the core of product 3 is as follows Figure 5 As shown in (c), although the binder hardness near the surface and the core of product 3 does not show an obvious hardness gradient distribution like product 1, the binder hardness near the surface of product 1 has been improved to a certain extent. In addition, compared with pure WC-Co-Ni cemented carbide without γ' precipitation phase strengthened binder, the binder hardness of product 3 has been significantly improved.
[0091] Example 4
[0092] This embodiment is a specific embodiment of preparing a gradient hard composite material product 4.
[0093] Step 1: Mix the raw materials
[0094] WC, Co, Ni and AlN are mixed in the following mass percentages;
[0095] WC: 45.44%; Co: 25%; Ni: 25%; AlN: 4.56%;
[0096] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, and AlN powders is ≥99.9%, and the particle size is 1-3μm.
[0097] Step 2: Ball mill drying
[0098] The first product 4 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 4.
[0099] Step 3: Dry pressing
[0100] The second product 4 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 4.
[0101] Step 4: Sintering
[0102] The third product 4 is placed in a graphite crucible and sintered in a vacuum to obtain product 4.
[0103] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0104] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0105] The vacuum sintering method is: heating from 1230°C to 1320°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0106] In this embodiment, a gradient hard composite material product 4 having a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 4 reaches 5.64GPa, and the core binder hardness HV0.01 reaches 6.12GP.
[0107] The microhardness HV0.01 distribution of the binder from the surface to the core of product 4 is as follows Figure 6As shown in (a), although the binder hardness near the surface and the core of product 4 does not show an obvious hardness gradient distribution, the binder hardness of product 4 is significantly improved compared with the pure WC-Co-Ni cemented carbide without γ' precipitation phase strengthened binder.
[0108] Example 5
[0109] This embodiment is a specific embodiment of preparing a gradient hard composite material product 5.
[0110] Step 1: Mix the raw materials
[0111] WC, Co, Ni, AlN and TaC are mixed in the following mass percentages to obtain a first product 5;
[0112] WC: 36.91%; Co: 25%; Ni: 25%; AlN: 4.56%; TaC: 8.53%;
[0113] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, AlN, and TaC powders is ≥99.9%, and the particle size is 1-3μm.
[0114] Step 2: Ball mill drying
[0115] The first product 5 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 5.
[0116] Step 3: Dry pressing
[0117] The second product 5 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 5.
[0118] Step 4: Sintering
[0119] The third product 5 is placed in a graphite crucible and sintered in a vacuum to obtain product 5.
[0120] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0121] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0122] The vacuum sintering method is: heating from 1230°C to 1320°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0123] In this embodiment, a gradient hard composite material product 5 having a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 5 reaches 5.27 GPa, and the core binder hardness HV0.01 reaches 5.92 GPa.
[0124] The microhardness HV0.01 distribution of the binder from the surface to the core of product 5 is as follows Figure 6 As shown in (b), the binder hardness of sample 5 near the surface is low, and the binder hardness of the core is relatively high. In addition, compared with the pure WC-Co-Ni cemented carbide without γ' precipitation phase strengthening binder, the binder hardness of product 5 is significantly improved.
[0125] Example 6
[0126] This embodiment is a specific embodiment of preparing a gradient hard composite material product 6.
[0127] Step 1: Mix the raw materials
[0128] WC, Co, Ni, AlN and NbC are mixed in the following mass percentages to obtain a first product 6;
[0129] WC: 36.41%; Co: 25%; Ni: 25%; AlN: 4.56%; NbC: 9.03%;
[0130] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, AlN, and NbC powders is ≥99.9%, and the particle size is 1-3μm.
[0131] Step 2: Ball mill drying
[0132] The first product 6 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80°C for 8 hours to obtain the second product 6.
[0133] Step 3: Dry pressing
[0134] The second product 6 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 6.
[0135] Step 4: Sintering
[0136] The third product 6 is placed in a graphite crucible and sintered in a vacuum to obtain product 6.
[0137] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0138] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0139] The vacuum sintering method is: heating from 1230°C to 1320°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0140] In this embodiment, a gradient hard composite material product 6 having a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 6 reaches 5.56 GPa, and the core binder hardness HV0.01 reaches 5.65 GPa.
[0141] The microhardness HV0.01 distribution of the binder from the surface to the core of product 6 is as follows Figure 6 As shown in (c), the binder hardness of sample 6 near the surface is low, and the binder hardness of the core is relatively high. In addition, compared with the pure WC-Co-Ni cemented carbide without γ' precipitation phase strengthening binder, the binder hardness of product 6 is significantly improved.
[0142] Example 7
[0143] This embodiment is a specific embodiment of preparing a gradient hard composite material product 7.
[0144] Step 1: Mix the raw materials
[0145] WC, Co, Ni and AlN are mixed in the following mass percentages to obtain a first product 7;
[0146] WC: 50.44%; Co: 15%; Ni: 30%; AlN: 4.56%;
[0147] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, and AlN powders is ≥99.9%, and the particle size is 1-3μm.
[0148] Step 2: Ball mill drying
[0149] The first product 7 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 7.
[0150] Step 3: Dry pressing
[0151] The second product 7 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 7.
[0152] Step 4: Sintering
[0153] The third product 7 is placed in a graphite crucible and sintered in a vacuum to obtain product 7.
[0154] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0155] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0156] The vacuum sintering method is: heating from 1230°C to 1350°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0157] In this embodiment, a gradient hard composite material product 7 with a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 7 reaches 4.90GPa, and the core binder hardness HV0.01 reaches 5.79Gpa. From the experimental results, it can be seen that the binder hardness near the surface of product 7 is slightly lower than the binder hardness of the core. In addition, compared with pure WC-Co-Ni cemented carbide without γ' precipitation phase reinforced binder, the binder hardness of product 7 is significantly improved.
[0158] Example 8
[0159] This embodiment is a specific embodiment of preparing a gradient hard composite material product 8.
[0160] Step 1: Mix the raw materials
[0161] WC, Co, Ni and AlN are mixed in the following mass percentages to obtain a first product 8;
[0162] WC: 50.44%; Co: 30%; Ni: 15%; AlN: 4.56%;
[0163] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, and AlN powders is ≥99.9%, and the particle size is 1-3μm.
[0164] Step 2: Ball mill drying
[0165] The first product 8 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 8.
[0166] Step 3: Dry pressing
[0167] The second product 8 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 8.
[0168] Step 4: Sintering
[0169] The third product 8 is placed in a graphite crucible and sintered in a vacuum to obtain product 8.
[0170] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0171] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0172] The vacuum sintering method is: heating from 1230°C to 1350°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0173] In this embodiment, a gradient hard composite material product 8 with a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 8 reaches 5.08GPa, and the core binder hardness HV0.01 reaches 5.63Gpa. From the experimental results, it can be seen that the binder hardness near the surface of product 8 is slightly lower than the binder hardness of the core. In addition, compared with pure WC-Co-Ni cemented carbide without γ' precipitation phase reinforced binder, the binder hardness of product 8 is significantly improved.
[0174] Example 9
[0175] This embodiment is a specific embodiment of preparing a gradient hard composite material product 9.
[0176] Step 1: Mix the raw materials
[0177] WC, Co, Ni and AlN are mixed in the following mass percentages to obtain a first product 9;
[0178] WC: 50.44%; Co: 15%; Ni: 30%; AlN: 4.56%;
[0179] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, and AlN powders is ≥99.9%, and the particle size is 1-3μm.
[0180] Step 2: Ball mill drying
[0181] The first product 9 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 9.
[0182] Step 3: Dry pressing
[0183] The second product 9 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining the third product 9.
[0184] Step 4: Sintering
[0185] The third product 9 is placed in a graphite crucible and sintered in a vacuum to obtain product 9.
[0186] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0187] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0188] The vacuum sintering method is: heating from 1230°C to 1320°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0189] In this embodiment, a gradient hard composite material product 9 with a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 9 reaches 5.14GPa, and the core binder hardness HV0.01 reaches 5.69Gpa. From the experimental results, it can be seen that the binder hardness near the surface of product 9 is slightly lower than the binder hardness of the core. In addition, compared with pure WC-Co-Ni cemented carbide without γ' precipitation phase reinforced binder, the binder hardness of product 9 is significantly improved.
[0190] Example 10
[0191] This embodiment is a specific embodiment of preparing a gradient hard composite material product 10.
[0192] Step 1: Mix the raw materials
[0193] WC, Co, Ni and AlN are mixed in the following mass percentages to obtain a first product 10;
[0194] WC: 50.44%; Co: 30%; Ni: 15%; AlN: 4.56%;
[0195] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co, Ni, and AlN powders is ≥99.9%, and the particle size is 1-3μm.
[0196] Step 2: Ball mill drying
[0197] The first product 10 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain the second product 10.
[0198] Step 3: Dry pressing
[0199] The second product 10 is placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining a third product 10.
[0200] Step 4: Sintering
[0201] The third product 10 is placed in a graphite crucible and sintered in a vacuum to obtain the product 10.
[0202] Before vacuum sintering, it is pretreated with denitrification. The specific process conditions are as follows:
[0203] The denitrification pretreatment method is: heating to 1230°C at a heating rate of 5-10°C / min, and keeping at this temperature for 120 minutes;
[0204] The vacuum sintering method is: heating from 1230°C to 1320°C at a heating rate of 2°C / min, keeping at this temperature for 60 minutes, and the vacuum degree is always kept less than or equal to 10Pa during the sintering process.
[0205] In this embodiment, a gradient hard composite material product 10 with a γ' nano-precipitation phase reinforced binder is obtained after vacuum sintering; after testing, the surface binder hardness HV0.01 of product 10 reaches 4.93GPa, and the core binder hardness HV0.01 reaches 5.57GPa. From the experimental results, it can be seen that the binder hardness near the surface of product 10 is slightly lower than the binder hardness of the core. In addition, compared with pure WC-Co-Ni cemented carbide without γ' precipitation phase reinforced binder, the binder hardness of product 10 is significantly improved.
[0206] Comparative Example
[0207] This comparative example is a specific example of preparing a reference product. In the comparative example, AlN and MC (M=Ta, Nb) are not added to the raw materials.
[0208] Step 1: Mix the raw materials
[0209] WC, Co and Ni are mixed in the following mass percentages to obtain a first reference material 1;
[0210] WC:50%; Co:25%; Ni:25%;
[0211] Among them, the purity of WC powder is ≥99.9%, and the particle size is 3-5μm; the purity of Co and Ni powder is ≥99.9%, and the particle size is 1-3μm;
[0212] Step 2: Ball mill drying
[0213] The first reference object 1 was put into a ball mill and milled for 6 hours at a ball-to-material ratio of 5:1, anhydrous ethanol as the grinding medium, and a rotation speed of 200 r / min until the powder was fully mixed and then dried in an oven at 80° C. for 8 hours to obtain a second reference object 1.
[0214] Step 3: Dry pressing
[0215] The second reference object 1 was placed in a mold, pressurized to 150 MPa, maintained at the pressure for 5 to 10 minutes, and then demolded to form a compact, thereby obtaining a third reference object 1.
[0216] Step 4: Sintering
[0217] The third reference object 1 was placed in a graphite crucible and vacuum sintered. The sintering process conditions were as follows: heating rate: 5-10°C / min, sintering temperature: 1350°C, sintering holding time: 120min, sintering vacuum degree: ≤5Pa.
[0218] The average HV0.01 of the control sample obtained by vacuum sintering is 3.28Gpa. The binder hardness HV0.01 of this sample is Figure 5 , Figure 6 comparative data.
[0219] It can be concluded from the above technical solutions and embodiments that the nano-precipitated phase reinforced binder gradient hard composite material and the preparation method thereof provided in the present application have the following advantages:
[0220] First, the nano-precipitated phase reinforced binder gradient hard composite material prepared by the technical solution provided in the present application has a gradient structure composed of WC, AlN, and a composite binder, which are: the surface hard phase is enriched and there is no AlN, and the core binder content is high. The hard phase-binder has a gradient distribution at the micron scale, has the advantages of high surface hardness and good core toughness, and achieves a good combination of hardness and toughness of the hard composite material.
[0221] In the preparation method provided in the present application, a heat preservation treatment is performed in the denitrification stage, and the AlN near the surface is first decomposed and releases nitrogen to the outside. As the denitrification process proceeds, a N element distribution gradient is formed in which the core is rich in N and the surface is poor in N. Due to the influence of the N element on the activity of the W element in the binder, the W element has a tendency to migrate from the N-rich core to the N-poor surface at this stage, and finally the W element forms an element gradient distribution in which the core is poor in W and the surface is rich in W.
[0222] During the cooling stage of the sintering process, due to the enrichment of W element in the binder near the surface, more WC grains will precipitate, thus forming a gradient structure with enriched hard phase on the surface and high binder content in the core.
[0223] Furthermore, in order to verify the above analysis results, samples with compositions of WC-25Co-25Ni-3Al, WC-25Co-25Ni-3Al-8Ta, and WC-25Co-25Ni-3Al-8Nb were vacuum sintered according to denitrification process parameters (keeping at 1230°C for 120 min) and sintering process parameters (keeping at 1320°C for 60 min).
[0224] After the sintered product was mounted and polished, the content of each element in the binder near the surface and core of the WC-25Co-25Ni-3Al sample was detected using a scanning electron microscope (SEM) equipped with energy dispersive X-ray spectroscopy (EDS). The contents of Al and W elements are as follows: Figure 1 The backscattered electron images (BSE) of the above three component samples are shown in Figure 2 shown.
[0225] from Figure 1 and Figure 2 It can be concluded that after the preparation method provided by the present application, a gradient distribution of elements is formed in the sample, and the gradient distributions of Al and W elements are coupled with each other, and finally form the following Figure 2 The surface is rich in hard phase and free of AlN, the core has a high binder content, and a gradient structure of hard phase-binder at the micron scale.
[0226] Second, the nano-precipitation phase reinforced binder gradient hard composite material prepared by the technical solution provided in the present application has a γ' nano-precipitation phase with an L12 structure in the binder. The γ' phase is a hard and brittle phase, precipitated in the γ matrix phase, and has a coherent relationship with the matrix phase. It can significantly improve the hardness of the binder while retaining the toughness of the matrix phase, thereby comprehensively improving the mechanical properties of the binder.
[0227] In the preparation method provided by the present application, a heat preservation treatment is performed in the denitrification stage, and AlN near the surface is first decomposed, and part of Al is dissolved in the binder. As the denitrification process proceeds, a N element distribution gradient is formed in which the core is rich in N and the surface is poor in N. Due to the influence of the N element on the activity of the Al and W elements in the binder, in the heating stage of the sintering process, as the dissolution proceeds, the Al element in the binder forms an element distribution gradient in which the core is rich in Al and the surface is poor in Al, and the W element forms an element distribution gradient in which the core is poor in W and the surface is rich in W.
[0228] Among them, Al, as a γ'-phase forming element, can increase the volume fraction of γ'-phase in the binder and increase the amount of γ'-phase. W, as a γ'-phase stabilizing element, can increase the solid solution temperature and volume fraction of γ'-phase. The Al content of the binder near the surface is relatively low, the W content is high, the γ'-phase solid solution temperature is high, the evolution temperature range of the γ'-phase is long during the entire cooling process, the evolution degree is high, and the final γ'-phase particle size is generally large; in contrast, the Al content of the binder in the core is relatively high, the W content is low, the γ'-phase solid solution temperature is low, and the final γ'-phase particle size is generally small.
[0229] Furthermore, to verify the above analysis conclusions, the sample with the composition of WC-25Co-25Ni-3Al was cut, mounted, polished and etched, and the morphology of the binder was observed under SEM. Figure 3 shown.
[0230] from Figure 3 It can be concluded that the size of the precipitated phase in the binder near the surface is significantly larger than that in the core. Due to the decomposition of AlN during the denitrification pretreatment during the sintering process, an N element gradient is formed inside the product, and the Al element subsequently forms an Al element gradient, thus forming a gradient distribution of the precipitated phase particle size in the binder.
[0231] Third, the nano-precipitation phase reinforced binder gradient hard composite material prepared by the technical solution provided in this application realizes gradient distribution at the hard phase, binder level and the binder internal matrix and nano-precipitation phase level respectively. The two are coupled with each other and synergistically strengthened, effectively improving the hardness and toughness of the material.
[0232] Furthermore, in order to verify the above conclusion, samples with compositions of WC-25Co-25Ni-3Al, WC-25Co-25Ni-3Al-8Ta, and WC-25Co-25Ni-3Al-8Nb were vacuum sintered according to denitrification process parameters (keeping at 1230°C for 120 min) and sintering process parameters (keeping at 1320°C for 60 min).
[0233] The sintered product was inlaid, polished and tested for Vickers hardness with a load of 200 gf from the surface to the core. The test results are as follows: Figure 4 shown.
[0234] from Figure 4 It can be concluded that all samples show a pattern of high surface macroscopic hardness and low core macroscopic hardness, which is consistent with Figure 2 The above results show that the sample prepared by the preparation method provided by the present application has the characteristics of surface hard phase enrichment and no AlN, and a hard phase-binder gradient distribution at the micrometer scale with a high content of core binder, and has the advantages of high surface hardness and good core toughness, achieving a good combination of hardness and toughness of the hard composite material.
[0235] Fourth, the preparation method provided in the present application is not only simple to operate, but also can control the thickness of the gradient layer by controlling the insulation time and the heating and cooling rates in the denitrification stage. In addition, high vacuum is also conducive to reducing the sintering temperature, thereby efficiently realizing the sintering preparation of nano-precipitation phase reinforced binder gradient hard composite material products.
[0236] In summary, the present application provides a nano-precipitated phase-reinforced binder gradient hard composite material, the raw materials of the composite material include: AlN powder, WC powder, metal binder and carbide, and the amount of aluminum element in the AlN powder is 2-6wt% composite material by mass percentage. The present application also provides a preparation method of the above composite material, including: raw material mixing, ball milling drying, dry pressing and sintering. In the technical scheme provided by the present application, a gradient hard composite material with surface hard phase enrichment, high core binder content and gradient distribution at the micrometer scale is prepared through the innovative design of raw materials and preparation methods; a nano-scale precipitation phase gradient distribution can also be formed in the binder through different sintering temperatures; the gradient distribution of the hard phase-binder at the micrometer scale and the gradient distribution of the ordered γ' precipitation phase in the binder at the nanometer scale are coupled and synergistically strengthened to achieve the improvement of the comprehensive performance of the product. Thereby effectively solving the technical defects in the prior art that cemented carbide is difficult to meet the performance requirements of harsh working conditions and hardness and toughness are difficult to coordinate.
[0237] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. At the same time, other implementation methods can be derived from the above-mentioned embodiments, so that structural and logical replacements and changes can be made without departing from the scope of this disclosure.
[0238] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A nano-precipitated phase reinforced binder gradient hard composite material, characterized in that: The raw materials of the composite material include: AlN powder, WC powder and metal binder, and the metal binder includes: Co and / or Ni; In terms of mass percentage, in the metal binder, the amount of Co element is 15-30wt% of the composite material, and the amount of Ni element is 15-30wt% of the composite material.
2. The composite material according to claim 1, characterized in that In terms of mass percentage, in the metal binder, the amount of Co element is 20-25wt% of the composite material, and the amount of Ni element is 20-25wt% of the composite material.
3. The composite material according to claim 1 or 2, characterized in that: The composite material further includes: carbide, and the carbide includes TaC and / or NbC.
4. The composite material according to claim 3, characterized in that The amount of transition metal elements in the carbide is 2-8wt% of the composite material.
5. The composite material according to claim 1 or 2, characterized in that: In terms of mass percentage, the amount of aluminum element in the AlN powder is 2-6wt% of the composite material.
6. A method for preparing the composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step 1, raw material mixing: the raw materials are mixed to obtain the first product; Step 2, ball milling and drying: the first product is ball milled and then dried to obtain the second product; Step 3, dry pressing: the second product is pressed into a green compact to obtain the third product: Step 4: Sintering: The third product is sintered under vacuum conditions to obtain a product.
7. The preparation method according to claim 6, characterized in that: In step 4, the sintering needs to undergo denitrification pretreatment.
8. The preparation method according to claim 7, characterized in that: The denitrification pretreatment method is as follows: the third product is heated to 1200-1250° C. at a heating rate of 5-10° C. / min, and the temperature is maintained for 60-120 minutes.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The sintering method comprises: heating the temperature to 1300-1400° C. at a heating rate of 2-5° C. / min, and maintaining the temperature for 30-120 minutes.